ANALISIS BUTIR SOAL UJIAN MAPEL SEJARAH (PEMINATAN) KELAS XII DI MAN SUMENEP TAHUN AJARAN 2021/2022 - Mochammad Ronaldy Aji Saputra; Joko Sayono (Jurnal Pendidikan Sejarah Indonesia, 2022)
PThis study aims to determine the quality of the Madrasah Final Examination (UAM) questions in the History subject (Specialization) at MAN Sumenep through item analysis. This research is a type of quantitative descriptive research. Analysis of the items to be examined are the results of tests of validity, reliability, level of difficulty, discriminating power, and deceptive power with the help of Microsoft Excel and SPSS 16.0. The results showed that the types of questions based on cognitive level were 10 percent LOTS questions, 18 percent MOTS questions, and 72 percent HOTS questions. Then based on the subject matter, it is 25 percent for class X and XI, and 50 percent for class XII. The level of validity (exceeding r-table) totaled 32 valid questions and 8 invalid items. The data reliability level of 0.409 is still inconsistent because it is still lacking 0.50. The level of difficulty resulted in 2 decisions, namely being rejected/revised because it was very easy with 12 questions and being accepted in the moderate category with 28 questions. The level of discriminating power resulted in 2 decisions, which were totally revised with an unsatisfactory category of 8 questions and totally revised/rejected by 32 questions. The distractor function works well because the multiple choices A, B, C, D, and E in questions are more than 5 percent. The results of the item analysis recommend that the UAM History Questions (Specialization) still need to be revised again with better quality questions.Penelitian ini bertujuan untuk mengetahui kualitas soal Ujian Akhir Madrasah (UAM) pada mapel Sejarah (Peminatan)di MAN Sumenep melalui analisis butir soal. Penelitian ini merupakan jenis penelitian deskriptif kuantitatif. Analisis butir soal yang akan diteliti adalah hasil uji validitas, reliabilitas, tingkat kesukaran, daya pembeda, dan daya pengecoh dengan berbantuan microsoft excel dan SPSS 16.0. Hasil penelitian menunjukan bahwa jenis soal berdasarkan tingkatan kognitifnya 10 persen soal LOTS, 18 persen soal MOTS, dan 72 persen soal HOTS. Kemudian berdarsarkan mapelnya sebanyak 25 persen kelas X dan XI, dan 50 persen kelas XII. Tingkat validitas (melebihi r-tabel) berjumlah 32 butir soal valid dan 8 butir soal tidak valid. Tingkat reliabilitas data sebesar 0,409 masih kurang konsisten karena masih kurang 0,50. Tingkat kesukaran menghasilkan 2 keputusan yaitu ditolak/direvisi karena sangat mudah sebanyak 12 soal dan diterima kategori sedang sebanyak 28 soal. Tingkat daya pembeda menghasilkan 2 keputusan yaitu direvisi total dengan kategori tidak memuaskan sebanyak 8 soal dan direvisi total/ditolak sebanyak 32 soal. Fungsi distraktor (pengecoh) dapat berfungsi baik karena pilihan ganda A, B, C, D, dan E pada soal lebih dari 5 persen. Hasil analisis butir soal merekomendasikan bahwa Soal UAM Sejarah (Peminatan) masih perlu direvisi kembali dengan kualitas soal yang lebih baik.